Identification of Bacterial Contamination in River Water Lulut in East Banjarmasin District - M. Anshori Mahboby (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Many people use river water for washing, bathing and some even still use traditional latrines. River water is starting to get polluted because it is contaminated with waste, especially bacterial contamination that occurs as a result of various kinds of waste from community activities around the river. Bacterial pollution in rivers is very dangerous if river water is used continuously by the community. The city of Banjarmasin accounts for the most diarrhea in South Kalimantan. The purpose of this study was to determine the value of contamination and the type of coliform bacteria in the water of the Martapura River, Sungai Lulut Village, East Banjarmasin District. The method used in this research is descriptive observation. All samples were positive with an average MPN value of >1100 MPN/g and were classified as rod-shaped gram-negative bacteria (bacillus) and suspected specifics of Escherichia Coli. The test results showed that the waters of the Martapura river, Lulut River Village, East Banjarmasin District, were contaminated with coliform bacteria that had passed the threshold of class 1 (1000 MPN/g) river requirements.